La participación ciudadana en el desarrollo comunitario de la parroquia Ecuador del cantón Huaquillas periodo 2020-2021 - Sánchez Cacay, Jorge Alejandro; Azuero Rivera, Keila Mishell (Machala : Universidad Técnica de Machala, 2022)
The following research project is about citizen participation in the community development that took place in Ecuador parish, Canton Huaquillas 2020 - 2021. In this context, there is evidence of a low level of citizen participation due to a poor directive leadership, as well as a limited planning process by the municipal government to promote the parish development. It is also found a prevalent social disorganization in the society. In this sense, the general objective of this research is based on determining the incidence of citizen participation in the community development of the parish aforementioned, along with the description of the characteristics that participation adopts in the field of social management and the identification of strategies for citizen participation. The methodology has been designed taking into account the hypothetical-deductive epistemological approach; analytical-synthetic method, mixed methodological approach, all of them using research instruments such as literature review to develop the theoretical framework, survey directed to 353 families, interview to the different presidents, and structured observation for the analysis of the characteristics of community development in the Ecuador parish. Based on the surveys' results obtained, it is determined that 32.3% of the inhabitants are unaware of the existence of planning in the parish, which suggests that the community is not involved in public affairs and that the neighborhood directives do not communicate their plans to the community. This situation is reflected in 69.7% of respondents who are not involved in problem solving and decision making. Similarly, 55% do not make use of the mechanisms of social inclusion, thus generating a weak development in the different neighborhoods of the parish. In addition, the problems of the 3009 families are not adequately solved. In addition, it is evident that 56.6% of those surveyed do not use citizen participation mechanisms such as the empty chair, participatory budgeting, public hearings and advisory councils. The 64% of the population is not involved in social control mechanisms such as citizen oversight, citizen observatories, community defenders and user committees. Regarding the results of the interview, in terms of citizen participation, there is a low level of participation and little use of mechanisms in integration activities such as debates and meetings for decision making, both in the community and in the local government. When it comes to community issues, the population expresses that there is an inadequate development, for this reason, the neighborhood leaders state that it is necessary to organize meetings with local authorities, create spaces for public opinion, build organizations, among other strategies, in order to achieve adequate progress in the community. Therefore, the proposal is to strengthen social cohesion through the mechanisms of citizen participation in Ecuador parish creating spaces for educational workshops, in addition there is the need to strengthen community leadership in social organizations for the design and implementation of projects to promote community progress through social efforts. To conclude, the research and the solution strategy is of significant importance, since it will allow the population to integrate into the social organizations and with itself, also to strengthen citizen empowerment and community leadership to address social management, using the mechanisms of citizen participation.
El presente trabajo de titulación trata sobre la participación ciudadana en el desarrollo comunitario de la parroquia Ecuador del cantón Huaquillas 2020 – 2021. En el contexto se evidencia un bajo nivel de participación ciudadana a causa de un deficiente liderazgo en las directivas, además, por limitado proceso de planificación por parte del GAD municipal para promover el desarrollo y por la desorganización social en la sociedad. En tal sentido, el objetivo general de la investigación se basa en determinación de la incidencia de la participación ciudadana en el desarrollo comunitario de la parroquia. Además, de la descripción de las características que adopta la participación en el ámbito de la gestión social y la identificación de las estrategias pertinentes para la participación. La metodología está articulada al enfoque epistemológico hipotético- deductivo, método analítico – sintético, enfoque metodológico mixto utilizando instrumentos de investigación como revisión bibliográfica para el desarrollo de la fundamentación teórica, encuesta, dirigida a 353 familias, entrevista, realizada a los diferentes presidentes, y la observación estructurada para el análisis de las características del desarrollo comunitario de la parroquia Ecuador. Con respecto a los resultados de la investigación empírica de la encuesta, se determina que un 32.3 % de los moradores, desconocen la existencia de planificaciones en la parroquia, por lo que da entender que la comunidad no se involucra en los asuntos públicos y que las directivas barriales no difunden las planificaciones en beneficio a la comunidad. Situación reflejada en un 69.7% de encuestados que no se involucran en la toma de decisiones y solución de problemas. De igual forma, se refleja que el 55% no hace uso de los mecanismos de inclusión social, generando así un débil desarrollo en las distintas ciudadelas que pertenecen a la parroquia Ecuador. Además de que los problemas de las 3009 familias no son solucionados de manera adecuada. Además, se evidencia que el 56.6% de los encuestados no utilizan los mecanismos de participación de ciudadana como la silla vacía, presupuesto participativo, audiencias públicas y consejos consultivos. Y un 64% de la población no se involucra en los mecanismos de control social como son las veedurías ciudadanas, observatorios ciudadanos, defensorías comunitarias y comités de usuarios. En cuanto a los resultados de la entrevista, en temas de participación ciudadana se destaca un bajo nivel de participación y escaso uso de los mecanismos en las actividades de integración como son los debates y reuniones para la toma de decisiones tanto en la comunidad como en el gobierno local. Y en temas comunitarios, la población expresa que existe inadecuado desarrollo, por tal motivo, los líderes barriales manifiestan pertinente organizar reuniones con las autoridades locales, crear espacios de opinión pública, conformar organizaciones, entre otras estrategias, con el fin de alcanzar un adecuado progreso en la comunidad. Por lo expuesto, se establece como propuesta el fortalecimiento de la cohesión social mediante los mecanismos de participación ciudadana de la parroquia Ecuador, para ello se plantea el desarrollo de talleres educativos, además de fortalecer el liderazgo comunitario en las organizaciones sociales para el diseño y ejecución de proyectos y consigo promover el progreso comunitario mediante gestiones sociales. Para dar por concluido, la investigación y la estrategia de solución reviste de significativa importancia, puesto que, permitirá a la población integrarse en las diversas organizaciones sociales y consigo, fortalecer el empoderamiento ciudadano y liderazgo comunitario para que hagan frente a las gestiones sociales, utilizando los mecanismos de participación ciudadana.
Keywords: PARTICIPACION CIUDADANA; DESARROLLO COMUNITARIO; INCLUSION SOCIAL; LIDERAZGO COMUNITARIO